Evidence of upwelling events at the northern Patagonian shelf break - Valla, Daniel (2015)
The Patagonian shelf break marks a transition between relative warm-fresh shelf waters and relative cold-salty Subantarctic Water advected northward by the Malvinas Current. From early spring to late autumn, the outer shelf region is characterized by a band of high chlorophyll concentration that sustains higher trophic levels, including significant fisheries. We analyze time series of current and water mass property observations collected at two moorings deployed at the shelf edge at 41 and 43.8 ºS to investigate what mechanisms lead to temperature variability at the shelf break, and their role on the nutrient supply to the upper layer. The in-situ data are combined with satellite-derived observations of sea surface temperature and chlorophyll-a to analyze a sharp cooling event at the outer shelf that lasted ten days and extended ~ 500 km along the outer shelf. The event is consistent with upwelling of cold waters through the base of the mixed layer. The vertical velocity required to explain the observed cooling is 13 to 29 m·day-1. Satellite derived sea surface temperature reveal additional cooling events of similar characteristics. Seventy-five percent of these events are concurrent with surface chlorophyll increase over a 5-day period suggesting that cooling events observed at the shelf break are associated with nutrient fluxes that promote the growth of phytoplankton.